Development of a Real-Time, Secure and Reliable Automobile Service Center - M. U. Dahanyake; N. M. Insaf; W. A. M. K. Perera; N. S. Jayasekara; D. I. De Silva; H. M. P. P. K. H. Samarasekara (International Journal of Engineering and Management Research, 2022)
Lack of ambition will prevent you from moving forward in life, as much like a car without petrol. The majority of people on earth is obsessed with automobiles. We have provided you with a web application for Real time automobile service that functions effectively on all the platforms. Occasionally, automobiles and other motorized vehicles require maintenance. They must be maintained clean, just as humans practice proper hygiene. They run on dirty streets and in polluted environment. They are subjected to loads that harm them since they travel on uneven roads with obstacles. Therefore, it is necessary to maintain automobiles and other motorized vehicles on a regular basis. This project aims to keep service centers running smoothly in terms of things like vehicle maintenance, customer quotation generation, vehicle servicing, spare parts sales, customer information, and customer feedback. The system is efficient at generating reports that will make service center routine maintenance easy. Additionally, it can handle car repairs, insurance, payments, delivery, etc. This project will be very helpful to customers who want to fix or repair their cars. As a result, we develop a software that is both compatible and unique.